Pengaruh Penambahan Kuning Telur pada Pengencer Susu Skim dan Lama Penyimpanan pada Suhu 5oC Terhadap Kualitas Spermatozoa Ayam Pelung - Yuniar, Tiara Utami; Saleh, Dadang Mulyadi; Mugiyono, Sigit (ANGON: Journal of Animal Science and Technology, 2021)
Background. The purpose of this research was to know the interaction effect between the addition of egg yolk to the skim milk diluent and storage time at 5oC on the motility, viability and abnormality of pelung rooster spermatozoa. Materials and methods. The materials of this research were collected fresh semen from 10 pelung roosters. This research used was experimental using a Randomized Completely Block Design (RCBD) with a 4 x 4 factorial pattern. In which egg yolk levels (p) was considered as the first factor and storage time (l) as the second factor. Each of the treatment was replicated three times. The first factor consisted of p1: 0% egg yolk + 100% skim milk, p2: 5% egg yolk + 95% skim milk, p3: 10% egg yolk + 90% skim milk, p4: 15% egg yolk + 85% skim milk while the second factor consisted of l1 (0 h), l2 (3 hrs), l3 (6 hrs), l4 (9 hrs). The variables observed were motility, viability and abnormality. Results. The results of the analysis of variance showed that the group or collecting period had a very significant effect (P<0.01) on the motility, viability and abnormality of the spermatozoa of pelung roosters. The results of the analysis of variance showed that the interaction between adding egg yolk to skim milk diluent and storage time at 5oC had no significant effect (P>0.05) while the addition of egg yolk to the skim milk diluent, and the storage time at 5oC had a very significant effect (P<0.01) on the motility, viability and abnormality of the spermatozoa of pelung rooster. The results of the HSD test showed that most comparisons between treatments showed very significant differences (P<0.01). Conclusion. The conclusion of this study is that there is no relation between addition egg yolk to the skim milk diluent and storage time at 5oC on motility, viability and abnormality of pelung rooster spermatozoa. The treatment of adding 10% egg yolk to the skim milk diluent resulted in the best motility and viability, while the treatment of adding 5% and 10% egg yolk to the skim milk diluent resulted in the lowest abnormality of pelung rooster spermatozoa. Storage time at 5oC for 0 hours resulted in the best motility, viability and abnormality of pelung rooster.